Relationship between Teachers’ Reflective Practices, Professional Development, and the Use of Formative Assessment at University Level - Dr. Fahd Naveed Kausar (Indus Journal of Social Sciences, 2025)
Teachers’ reflective practices, professional development, and the use of formative assessment are interconnected elements that enhance instructional quality and promote continuous improvement. By integrating these practices, educators can better address student needs and foster more effective learning environments. The objectives of the study were to identify the level of teachers’ reflective practices, professional development, and the use of formative assessment, to find out the relationship between teachers’ reflective practices, professional development, and the use of formative assessment. The study employed a descriptive research design. The population consisted of all public and private 39 universities in Lahore District. A multistage simple random sampling technique was utilized to ensure comprehensive representation. The instrument of the study was questionnaire. Primary data was collected using the administered questionnaires, which were distributed to the selected participants. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS). Descriptive (mean and standard deviation) and inferential statistics (Pearson r) was used. The findings of the study revealed that there was moderate positive significant relationship between teachers’ reflective practices and their professional development at university level. There was highly significant positive relationship between teachers’ reflective practices and the use of formative assessment at university level. And also, there was moderate positive significant relationship between professional development and use of formative assessment at university level.